2013
DOI: 10.12701/yujm.2013.30.1.47
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pancytopenia with Hyperthyroidism

Abstract: There has been an increase in the number of reports of atypical manifestations of Graves' disease (GD), such as jaundice, anemia, thrombocytopenia and leukopenia. Pancytopenia also rarely occurs in GD. In this paper, a case of pancytopenia with GD that was successfully treated with an anti-thyroid drug is reported. In this case, a 69-year-old woman showed pancytopenia with a normal peripheral blood smear, bone marrow aspiration smear and bone marrow biopsy. Her thyroid function test and thyroid scintigraphy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…It appears that anemia is the most associated cytopenia (10%-34%) of patients with thyrotoxicosis. [1][2][3] Leukopenia is reported in 15% to 30% of untreated thyrotoxicosis, and thrombocytopenia is rarely observed in 2% to 5% of thyrotoxicosis cases. 1,3 The association between thyrotoxicosis and pancytopenia is a rarely described in the literature (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears that anemia is the most associated cytopenia (10%-34%) of patients with thyrotoxicosis. [1][2][3] Leukopenia is reported in 15% to 30% of untreated thyrotoxicosis, and thrombocytopenia is rarely observed in 2% to 5% of thyrotoxicosis cases. 1,3 The association between thyrotoxicosis and pancytopenia is a rarely described in the literature (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…19 Moreover, a relative lymphocytosis with cross-antigenicity between human TSH receptors and polynuclear neutrophils has been described with formation of a characteristic blood finding of Graves disease called Kocher blood picture. 1 EMA Kyritsi et al 20 found that thyroidopathy represents the most common disorder among apparently healthy patients with mild-to-moderate neutropenia. They showed significant patterns of parameters and markers of immunity and remarkable correlations between T3 levels and absolute neutrophil counts, TSH levels and absolute CD4+ counts, T4 levels and absolute CD4+ counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, single lineage abnormalities (anemia, leukopenia, or thrombocytopenia) are more common in patients with hyperthyroidism (34%, 5.8%, and 3.3%, resp.) [ 5 , 10 ]. Leukopenia with a relative lymphocytosis is not an uncommon blood abnormality in GD, named “Kocher's blood picture.” [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hematopoietic system is greatly affected by the thyroid state, and thyrotoxicosisinduced changes can affect all three hematopoietic cell lineages. The most common presentation is anemia [2]. Pancytopenia has been reported in few cases in the literature, and most cases were related to Graves' disease, but they are not usually catastrophic [3].…”
Section: Discussionmentioning
confidence: 99%